Study the adsorption of lignin on surface of poly vinyl chloride (Journal of the College of Basic Education, 2022)
In this work, polyvinyl chloride(PVC) was utilized as a strong adsorbent for the expulsion of lignin from fluid arrangement utilizing a shower techniques. The got an outcome infer that the lignin adsorbs onto PVC are driven by entropy impact, exothermic and nonspontaneous forms, additionally, the outcomes have as demonstrated that Freundlich isotherm fitted a harmony information well. as per Dubinin – Radushkevich isotherms the adsorption limit of PVC (qmax) is 2.8303 mg/g, the mean free vitality (EDR) esteem an ascertained by examinations of a balance information with Dubinin – Radushkevicha condition show that the adsorption components are hydrogen holding .the lignin was expelled by (39.2%) at PH measure up to 2 and at 30 Co .Key word: lignin, poly vinyl chloride, adsorption